Advantages and Disadvantages of the Single European Patent - Glazer, Klara (Naše gospodarstvo/Our economy, 2015)
In February 2013, the European Union successfully completed more than 30 years of negotiations and formally signed an agreement establishing a single European patent. The agreement brought about a more competitive patent law compared with that in the United States and Japan. The agreement resulted in a number of advantages, especially for small and medium-sized enterprises, such as the reduction of costs by as much as 80%, simplification of procedures, and the adoption of the Unified Patent Court. With the new unitary patent, intellectual property will grow in importance. Yet experts warn that the new patent results in new forms of unwanted behavior, such as forum shopping and the emergence of patent trolls. This study presents both sides—the pros and cons—to predict the effects on business and cover the widest possible range of experts, providing their views on the topic.
Keywords: Single European patent; single patent court; reduce costs; patent trolls; simplified procedures; forum shopping; European Union